Primary resistance of hepatitis B virus to nucleoside and nucleotide analogues. Issue 2 (14th November 2018) - Chevaliez, Stéphane; Rodriguez, Christophe; Poiteau, Lila; Soulier, Alexandre; Donati, Flora; Darty‐Mercier, Mélanie; Pioche, Corinne; Leroy, Vincent; Brodard, Véronique; Zoulim, Fabien; Brouard, Cécile; Larsen, Christine; et al.
Summary: Nucleoside and nucleotide analogues (NUCs) targeting hepatitis B virus are capable of selecting resistant viruses upon long‐term administration as monotherapies. The prevalence of resistance‐associated substitutions (RASs) and fitness‐associated substitutions at baseline of NUC therapy and their impact on treatment responses remain unknown. A total of 232 treatment‐naïve patients chronically infected with hepatitis B virus (HBV) consecutively referred for the first time to one of French reference centres were included. The nearly full‐length HBV reverse transcriptase was sequenced by means of deep sequencing, and the sequences were analysed. RASs were detected in 25% of treatment‐naïve patients, generally representing low proportions of the viral quasispecies. All amino acid positions known to be associated with HBV resistance to currently approved NUCs or with increased fitness of resistant variants were affected, except position 80. RASs at positions involved in lamivudine, telbivudine and adefovir resistance were the most frequently detected. All patients with RASs detectable by next‐generation sequencing at baseline who were treatment‐eligible and treated with currently recommended drugs achieved a virological response. The presence of pre‐existing HBV RASs has no impact on the outcome of therapy if potent drugs with a high barrier to resistance are used.